Serum Zinc, Total & Free PSA, Free/Total PSA Ratio and Prostate Cancer Association: A Case Control Study (Anwer Khan Modern Medical College Journal, 2013)
This case case control study was undertaken to see if there is any association of serum Zinc level with histologically diagnosed prostatic cancer patients. Also to re-establish the importance of estimation of serum Prostate specific antigen PSA, (Total, Free and ratio between free and total) in prostate cancer patients. It was evident from the present study that serum Zinc level has got statistically significant difference between control and prostate cancer patients (p